2018
DOI: 10.1103/physrevd.97.123536
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing cosmology in f(R,T) gravity

Abstract: A cosmological model with a specific form of the Hubble parameter is constructed in a flat homogeneous, and isotropic background in the framework of f (R, T ) gravity, where R is the scalar curvature and T is the trace of the stress-energy-momentum tensor. The proposed functional form of the Hubble parameter is taken in such a way that it fulfills the successful bouncing criteria to find the solution of the gravitational field equations provided the Universe is free from initial singularity. The various constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 77 publications
2
62
0
Order By: Relevance
“…The electronic structure of solid molecular hydrogen have mainly been investigated by means of density-functional theory (DFT)-based methods, [16][17][18][19][20][21][22][23][24][25] as well as using the quasiparticle (QP) approach. [15,26] Although DFT-based methods are usually able to describe the crystal structures and relative total energies of the relevant phases, their insufficiencies are more apparent in the case of band-gap calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of solid molecular hydrogen have mainly been investigated by means of density-functional theory (DFT)-based methods, [16][17][18][19][20][21][22][23][24][25] as well as using the quasiparticle (QP) approach. [15,26] Although DFT-based methods are usually able to describe the crystal structures and relative total energies of the relevant phases, their insufficiencies are more apparent in the case of band-gap calculations.…”
Section: Introductionmentioning
confidence: 99%
“…a. Zero-field muon spin relaxation Firstly, time-reversal symmetry breaking was investigated by ZF-µSR, as has been seen in other NCS superconductors [11,[28][29][30][31][32]. In superconductors with broken TRS, either the spin or orbital parts of the Cooper pairs are non-zero, which results in the appearance of the small magnetic field below the transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Noncentrosymmetric superconductors have been recognized as good candidates to search for broken TRS. To date, TRS breaking have been found in NCS superconductors, such as LaNiC 2 [11], Re 6 X (X * rpsingh@iiserb.ac.in = Ti,Zr,Hf) [28][29][30], locally noncentrosymmetric SrPtAs [31] and La 7 Ir 3 [32]. This number is very small, if compared to the extent of NCS superconductors studied so far [33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that biaxial strain could suppress indium phase separation in InGaN/GaN double heterojunction structure and thus provides an important channel to improve the quality of InGaN film with high In composition. [13][14] The strategy of InGaN/GaN multiple quantum well (MQW) embedded within the intrinsic region of conventional p-i-n structure was proposed and played a positive role for InGaN SCs. Sheu et al showed that InGaN/GaN superlattice structure had obvious advantages over single thick film of InGaN, [15] which was further proven by Cavassilas et al in theory.…”
Section: Introductionmentioning
confidence: 99%